Beyond the invisible hand : groundwork for a new economics - Basu, Kaushik (Princeton University Press, 2010)
One of the central tenets of mainstream economics is Adam Smith's proposition that, given certain conditions, self-interested behavior by individuals leads them to the social good, almost as if orchestrated by an invisible hand. This deep insight has, over the past two centuries, been taken out of context, contorted, and used as the cornerstone of free-market orthodoxy. In Beyond the Invisible Hand, Kaushik Basu argues that mainstream economics and its conservative popularizers have misrepresented Smith's insight and hampered our understanding of how economies function, why some economies fail.